Effects of different irrigation amounts on soil structure in newly cultivated land on the Loess Plateau - Hongyi Pan; Qize Song; Luyao Yi; Bo Li; Rutian Bi (PLoS ONE, 2025)
It is imperative to promote water-saving irrigation technology and develop newly cultivated land in the Loess Plateau. This study focused on the interaction between roots and soil to examine the effects of different amounts of irrigation on soil structure of newly cultivated land. Herein, five irrigation levels were set, i.e., sufficient irrigation (W100), mild deficit irrigation (W80), moderate deficit irrigation (W60), severe deficit irrigation (W40), and rain-fed (RF). Physical properties and structural stability indexes of the rhizosphere soil were measured, and their relationship with plant root morphology were analyzed. The results showed that the soil structure under the high irrigation amount group (W80 and W100) was relatively stable. The average particle density of soil in each plot decreased significantly after the experiment, while the soil total porosity remained unchanged in W80 and W100 treatments. The proportion of large aggregates, the mean weight diameter, and the geometric mean diameter of soil significantly reduced in the low irrigation amount group (RF, W40, and W60). In contrast, the W100 and W80 treatments inhibited the decline in soil aggregate stability. Change in the generalized soil structure index (GSSI) and soil three-phase structure distance (STPSD) of W100 and W80 treatments were not significant, before and after the experiment. These results suggested that the soil in newly cultivated land treated with sufficient and mild deficit irrigation was closer to the ideal state for crops growing. Path analysis identified the average soil moisture content had the greatest negative effect on STPSD primarily through the root length, root surface area, and root dry weight. In conclusion, irrigation amount occupies a dominant position among all factors influencing soil structure considered in the study. And the mild deficit irrigation is suitable for agricultural cultivation in the Loess Plateau area, from the soil structure protection and water-saving perspectives.